Acute Rheumatic Fever: A Disease of the Past? - Robert L. Myette (Case Reports in Infectious Diseases)
Introduction. Acute rheumatic fever (ARF) is a manifestation of the nonsuppurative sequelae of Streptococcus pyogenes infection. Herein, two cases of ARF are presented to highlight that this disease is present in urban cities, can be diagnosed in otherwise healthy children, and that its diagnosis may be challenging, or marred with confounders, leading to delays in diagnosis. Case Report. Two unrelated children, age 7 and 9, presented to an urban hospital in Canada with unique manifestations of ARF. Diagnosis of ARF in the first patient was interrupted by a course of steroids which masked symptoms leading to therapeutic delays. The second patient presented with facial droop and symptoms thought to be viral, thus leading to misdiagnosis as Bell’s palsy. Discussion/Conclusion. ARF is more common in underserviced and marginalized populations, which may lead clinicians in urban centers to overlook signs or symptoms suggestive of ARF because they no longer see this condition routinely, or they believe it is a disease of the past.